Relation between spiritual intelligence and clinical competency of nurses in Iran - Hossein Karimi-Moonaghi; Akram Gazerani; Saeed Vaghee; Hassan Gholami; Amir Reza Salehmoghaddam; Raheleh Gharibnavaz (Wolters Kluwer Medknow Publications, 2015)
Background: Clinical competency is one of the most important requirements in nursing profession, based on which nurses are assessed. To obtain an effective and improved form of clinical competency, several factors are observed and monitored by the health educational systems. Among these observed factors, spiritual intelligence is considered as one of the most significant factors in nurses' success and efficacy. In this study, it is aimed to determine the spiritual intelligence status and its relationship with clinical competency. Materials and Methods: The descriptive-correlational research was carried out on 250 nurses in Mashhad educational hospitals, selected by multi-stage sampling. Demographic, clinical competency, and spiritual intelligence questionnaires were used for data collection and 212 questionnaires were analyzed. Results: About 53.3% of nurses obtained above average scores in spiritual intelligence. Clinical competency was evaluated by both self-evaluation and head nurse evaluation methods. Most nurses (53.8%) were having good level of clinical competency based on self-evaluation, 48.2% were at average level based on head nurse evaluation, and 53.3% were at average level based on overall score. A significant correlation was found between spiritual intelligence and clinical competency. Conclusions: In this study, the positive significant correlation between nurses' spiritual intelligence and their clinical competency is investigated. Because of the positive effects of spiritual intelligence on nurses' clinical competency and quality of care, it is recommended to develop nurses' spiritual intelligence during their education and by way of continuous medical education.